Fe / Zr-MOF-assisted synthesized solid superacid ZSM-5 composite material as well as preparation method and application of Fe / Zr-MOF-assisted synthesized solid superacid ZSM-5 composite material
The solid super acid @ZSM-5 composite material assisted by Fe/Zr-MOF synthesis solves the problem of insufficient adsorption capacity of existing composite materials to low-concentration ammonia gas, achieves efficient adsorption and good cycle regeneration performance, and significantly improves the adsorption performance of the material.
Patent Information
- Application Number
- CN202510109480.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-11
AI Technical Summary
The adsorption capacity of the composite materials formed by the combination of existing traditional adsorption materials to low-concentration ammonia gas still needs to be further improved.
Using the solid superacid @ZSM-5 composite material assisted by Fe/Zr-MOF, the in-situ growth of Fe/Zr-MOF, calcination carbonization and sulfation modification steps, composite materials with high adsorption efficiency and good cycle regeneration performance were prepared.
It has achieved efficient adsorption of low-concentration ammonia gas, with an adsorption capacity of 692mg/g, and it still showed good adsorption performance after 5 cycles of adsorption, which significantly improved the adsorption performance and renewable performance of the material.
Smart Images

Figure CN119793391A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a Fe / Zr-MOF-assisted synthesized solid superacid@ZSM-5 composite material and a preparation method and application thereof. Background Art
[0002] Ammonia is an important industrial raw material, playing a key role in fertilizers, pharmaceuticals and synthetic fibers. However, its excessive emissions will not only lead to environmental problems such as haze, eutrophication and soil acidification, but also pose a threat to human health. The concentration of ammonia that directly endangers life or health is 300ppm. Therefore, the development of effective ammonia adsorption technology is crucial for environmental protection and efficient utilization of resources. Ammonia adsorption materials mainly include traditional adsorption materials such as activated carbon, molecular sieves and organic resins, new adsorption materials such as porous organic polymers and metal organic frameworks (MOFs). Traditional materials have the advantages of low cost and material stability, while new materials have the advantages of controllable structure and diverse adsorption sites. Among them, MOFs, as a new adsorption material, show great potential in treating gaseous pollutants.
[0003] By combining the respective advantages of traditional adsorbent materials and new adsorbent materials, composite materials with better performance can be prepared. The literature [International Journal of Energy Research, 2023, 1: 2282746] reported MOF-5@activated carbon and Cu-BDC@activated carbon composite materials for the adsorption of methane. The methane adsorption capacity of 40wt% MOF-5@activated carbon was the highest, and the methane adsorption capacity was 7.3mmol / g at 35bar pressure and 298K temperature. The literature [Journal of CO2Utilization, 2022, 64: 102182] reported an in-situ prepared ZIF-8@MCM-41 composite material for the adsorption of CO2. The composite material exhibited the physical properties of its parent material, and the CO2 adsorption capacity reached 3.15mmol / g. The Chinese invention patent with the authorization announcement number CN113908809B discloses an activated carbon embedded MOF adsorption material and its application in the adsorption of organic sulfur. The MOF is synthesized in the pores of the activated carbon by in-situ synthesis technology. The pore size of the activated carbon is adjusted by MOF to match the molecular size of the adsorbate, thereby improving its adsorption capacity. The adsorption capacity of methyl sulfide can reach 1120 mg / g. The Chinese invention patent with the authorization announcement number CN118122290B discloses a Cu-ZSM-5 / HKUST-1 composite material, which can improve the thermal stability of the material, increase the specific surface area of the adsorption material, enhance the adsorption performance, expand the adsorption range of VOCs, and the toluene removal efficiency can reach 98.3%. In summary, the combination of traditional adsorption materials and new adsorption materials can achieve more excellent adsorption performance, providing an innovative idea for creating a new generation of adsorbents. However, the adsorption capacity of the composite material formed by the combination of the existing traditional adsorption materials and the new adsorption materials for low-concentration NH3 still needs to be further improved.
[0004] In view of this, it is necessary to develop a composite material formed by combining traditional adsorption materials with new adsorption materials, which has high adsorption efficiency, strong adsorption capacity for low-concentration NH3, and strong recycling and regeneration ability. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and to provide a Fe / Zr-MOF-assisted synthesized solid superacid @ZSM-5 composite material and a preparation method thereof, comprising a step of in-situ growth of Fe / Zr-MOF on ZSM-5, a calcination carbonization step, and a sulfation modification step, to finally obtain a Fe / Zr-MOF-assisted synthesized solid superacid @ZSM-5 composite material; the composite material has good stability, can achieve co-adsorption of ammonia, and can effectively adsorb low-concentration ammonia.
[0006] The present invention provides a method for preparing a Fe / Zr-MOF-assisted solid superacid@ZSM-5 composite material, comprising the following steps:
[0007] Step S1, preparation of Fe / Zr-MOF@ZSM-5: drying the support under vacuum at 80-100°C for 8-12h, pouring it into a formic acid solution, ultrasonicating it for 30-60min to form a solution A, dissolving FeCl3·6H2O and ZrCl4 in N,N-dimethylformamide to form a solution B, adding the solution B to the solution A, ultrasonicating it for 30-60min, adding 1,3,5-benzenetricarboxylic acid thereto, ultrasonicating it for 1-2h, transferring it to a high-pressure reactor, and heating it at 120-150°C for 24-48h; finally, washing the obtained sample with N,N-dimethylformamide and methanol for 3-5 times respectively, and drying it under vacuum at 80-100°C overnight to obtain Fe / Zr-MOF@ZSM-5;
[0008] Step S2, preparing Fe2O3-ZrO2@ZSM-5: placing the Fe / Zr-MOF@ZSM-5 prepared in step S1 in a tube furnace for calcination to obtain Fe2O3-ZrO2@ZSM-5;
[0009] Step S3: Preparation of SO 42 - / Fe2O3-ZrO2@ZSM-5: Add Fe2O3-ZrO2@ZSM-5 into sulfuric acid solution, soak for 30-180 min, filter to obtain solid, dry at 100-120℃ overnight, and finally calcine at 500-600℃ in air atmosphere for 3-6 h to obtain SO 42 - / Fe2O3-ZrO2@ZSM-5;
[0010] Preferably, the carrier in step S1 is ZSM-5.
[0011] Preferably, the mass ratio of ZrCl4, FeCl3·6H2O, 1,3,5-benzenetricarboxylic acid, formic acid, N,N-dimethylformamide, and ZSM-5 in step S1 is 1:(1-2):(1-3):(35-40):(25-30):(2-4).
[0012] Preferably, the calcination in step S2 is specifically: heating to 500-600° C. at a heating rate of 5-10° C. / min in an air atmosphere, and the calcination time is 4-8 h.
[0013] Preferably, the concentration of the sulfuric acid solution in step S3 is 1-3 mol / L.
[0014] Preferably, the mass ratio of Fe2O3-ZrO2@ZSM-5 and sulfuric acid solution in step S3 is 1:(20-50).
[0015] Another object of the present invention is to provide a Fe / Zr-MOF-assisted synthesized solid superacid@ZSM-5 composite material prepared by the preparation method of the Fe / Zr-MOF-assisted synthesized solid superacid@ZSM-5 composite material.
[0016] Another object of the present invention is to provide an application of the Fe / Zr-MOF-assisted synthesized solid superacid@ZSM-5 composite material in ammonia adsorption.
[0017] Due to the application of the above technical solution, the present invention has the following beneficial effects:
[0018] (1) The preparation method of the Fe / Zr-MOF-assisted solid superacid @ZSM-5 composite material disclosed in the present invention comprises a step of in-situ growth of Fe / Zr-MOF on ZSM-5, a step of calcination and carbonization, and a step of sulfation modification; the process is simple, the operation is convenient, the preparation efficiency and the qualified rate of finished products are high, the dependence on equipment is low, it is suitable for continuous large-scale production, and it has a high value of promotion and application.
[0019] (2) The Fe / Zr-MOF-assisted solid superacid @ZSM-5 composite material disclosed in the present invention, through the combination of traditional adsorption materials and new adsorption materials, cooperates with each other, and has an adsorption capacity of 692 mg / g for low-concentration ammonia. After 5 cycles of adsorption, it shows good regenerative performance.
[0020] (3) The Fe / Zr-MOF-assisted solid superacid @ZSM-5 composite material disclosed in the present invention is Fe2O3-ZrO2@ZSM-5 obtained by pyrolysis of Fe / Zr-MOF modified by sulfation, and the Bronsted acid sites and Lewis acid sites that appear can achieve co-adsorption of low-concentration ammonia. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The ammonia adsorption kinetic curves of the products of the embodiments of the present invention and the comparative examples;
[0022] Figure 2 It is a performance diagram of ammonia adsorption cycle of the products of the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION
[0023] In order to enable those skilled in the art to better understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained under the premise of equivalent changes and modifications made by ordinary technicians in the field should belong to the scope of protection of the present invention.
[0024] In the description of the present invention, it should be understood that the instruments, equipment or devices involved are all conventional instruments, equipment or devices unless otherwise specified; the raw materials or compounds involved are all commercially available conventional raw materials or compounds unless otherwise specified; the methods involved are all conventional methods unless otherwise specified.
[0025] Example 1
[0026] This embodiment provides a method for preparing a Fe / Zr-MOF-assisted solid superacid@ZSM-5 composite material, the steps are as follows:
[0027] (1) Preparation of Fe / Zr-MOF@ZSM-5
[0028] 4g ZSM-5 was dried under vacuum at 80℃ for 8h, poured into 70g formic acid solution, and dispersed evenly by ultrasonication for 30min to form solution A. l3 6H2O and 2g ZrCl4 were dissolved in 50g N,N-dimethylformamide (DMF) to form solution B, which was added to solution A and ultrasonicated for 30min. 2g 1,3,5-benzenetricarboxylic acid was added to solution A and ultrasonicated for 1h. Solution A was transferred to a high-pressure reactor and heated at 120℃ for 24h. Finally, the obtained sample was washed with DMF and methanol for 3 times respectively and dried under vacuum at 80℃ overnight to obtain Fe / Zr-MOF@ZSM-5.
[0029] (2) Preparation of Fe2O3-ZrO2@ZSM-5
[0030] The prepared Fe / Zr-MOF@ZSM-5 was placed in a tube furnace and heated to 500°C at a heating rate of 5°C / min under air atmosphere for 4 h to obtain Fe2O3-ZrO2@ZSM-5.
[0031] (3) Preparation of SO 42 - / Fe2O3-ZrO2@ZSM-5
[0032] 2 g Fe2O3-ZrO2@ZSM-5 was added to 40 g 1 mol / L sulfuric acid solution and soaked for 30 min. The solid was then filtered and dried at 100 °C overnight. Finally, it was calcined at 500 °C in air for 3 h to obtain SO 42 - / Fe2O3-ZrO2@ZSM-5.
[0033] Example 2
[0034] This embodiment provides a method for preparing a Fe / Zr-MOF-assisted solid superacid@ZSM-5 composite material, the steps are as follows:
[0035] (1) Preparation of Fe / Zr-MOF@ZSM-5
[0036] 4g ZSM-5 was dried under vacuum at 100℃ for 12h, poured into 40g formic acid solution, and dispersed evenly by ultrasonication for 60min to form solution A. 2g FeCl3·6H2O and 1g ZrCl4 were dissolved in 30g N,N-dimethylformamide (DMF) to form solution B. Solution B was added to solution A and ultrasonicated for 60min. 3g 1,3,5-benzenetricarboxylic acid was added to solution A and ultrasonicated for 2h. Solution A was transferred to a high-pressure reactor and heated at 150℃ for 48h. Finally, the obtained sample was washed 5 times with DMF and methanol respectively, and dried overnight under vacuum at 100℃ to obtain Fe / Zr-MOF@ZSM-5.
[0037] (2) Preparation of Fe2O3-ZrO2@ZSM-5
[0038] The prepared Fe / Zr-MOF@ZSM-5 was placed in a tube furnace and heated to 600°C at a heating rate of 10°C / min under air atmosphere for 8 h to obtain Fe2O3-ZrO2@ZSM-5.
[0039] (3) Preparation of SO 42 - / Fe2O3-ZrO2@ZSM-5
[0040] 2 g Fe2O3-ZrO2@ZSM-5 was added to 100 g 3 mol / L sulfuric acid solution and soaked for 180 min. The solid was then filtered and dried at 120 °C overnight. Finally, it was calcined at 600 °C in air for 6 h to obtain SO 42 - / Fe2O3-ZrO2@ZSM-5.
[0041] Example 3
[0042] This embodiment provides a method for preparing a Fe / Zr-MOF-assisted solid superacid@ZSM-5 composite material, the steps are as follows:
[0043] (1) Preparation of Fe / Zr-MOF@ZSM-5
[0044] 2g ZSM-5 was dried under vacuum at 100℃ for 12h, poured into 38g formic acid solution, and dispersed evenly by ultrasonication for 60min to form solution A. 1.15g FeCl3·6H2O and 1g ZrCl4 were dissolved in 28g N,N-dimethylformamide (DMF) to form solution B. Solution B was added to solution A and ultrasonicated for 50min. 1.5g 1,3,5-benzenetricarboxylic acid was added to solution A and ultrasonicated for 1h. Solution A was transferred to a high-pressure reactor and heated at 140℃ for 36h. Finally, the obtained sample was washed with DMF and methanol for 3 times, respectively, and dried under vacuum at 80℃ overnight to obtain Fe / Zr-MOF@ZSM-5.
[0045] (2) Preparation of Fe2O3-ZrO2@ZSM-5
[0046] The prepared Fe / Zr-MOF@ZSM-5 was placed in a tube furnace and heated to 550°C at a heating rate of 5°C / min under air atmosphere for 4 h to obtain Fe2O3-ZrO2@ZSM-5.
[0047] (3) Preparation of SO 42 - / Fe2O3-ZrO2@ZSM-5
[0048] 2 g Fe2O3-ZrO2@ZSM-5 was added to 60 g 2 mol / L sulfuric acid solution and soaked for 120 min. The solid was then filtered and dried at 100 °C overnight. Finally, it was calcined at 500 °C in air for 4 h to obtain SO 42 - / Fe2O3-ZrO2@ZSM-5.
[0049] Comparative Example 1
[0050] The difference between this comparative example and Example 1 is that the product is not modified by sulfation.
[0051] The ammonia adsorption performance of the composite materials prepared in Examples 1-3 and Comparative Example 1 was tested as follows:
[0052] When evaluating the ammonia adsorption performance, the following experimental steps are used: First, fill the sample onto the filter screen in the quartz tube. Start the fan and mass flow meter to adjust the gas flow rate, and then test the ammonia adsorption performance of the material. During the test, the upstream concentration of ammonia is maintained at 10ppm, the flow rate is controlled at 10L / min, and the resistance during the test does not exceed 100pa. The specific test data is recorded in Table 1.
[0053] Table 1 Ammonia adsorption performance test
[0054] project Weight(g) Air volume (L / min) Resistance (Pa) Initial efficiency (%) Adsorption capacity (mg / g) Example 1 3 20 78 98.1 635 Example 2 3 20 82 98.5 664 Example 3 3 20 80 99.3 692 Comparative Example 1 3 20 86 81.8 149
[0055] As can be seen from Table 1, the Fe / Zr-MOF-assisted solid superacid@ZSM-5 composite material has excellent low-concentration ammonia adsorption performance, among which the maximum ammonia adsorption capacity can reach 692 mg / g at 270 min. Compared with the unsulfated sample, the performance is significantly improved. The sulfated material improves the pore structure, which is conducive to the diffusion and adsorption of ammonia molecules. At the same time, the acidic functional groups on the surface of the material are increased, and solid superacids are formed. The more and stronger Bronsted acid sites and Lewis acid sites are the key to achieving low-concentration ammonia adsorption.
[0056] Depend on Figure 1 It can be seen that the composite material prepared in Example 3 has the largest ammonia adsorption capacity and the fastest adsorption rate. The material not modified by sulfation reaches adsorption saturation in about 240 minutes, indicating that the pore volume of the material is increased after sulfation modification.
[0057] Figure 2 It shows that the solid superacid@ZSM-5 composite material still has excellent ammonia adsorption performance after 5 cycles of adsorption, showing good regeneration performance, while the performance of the unsulfated sample is slightly reduced after 5 cycles of adsorption, indicating that the Fe2O3-ZrO2@ZSM-5 composite material also has good cyclic regeneration performance.
[0058] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a Fe / Zr-MOF-assisted solid superacid @ZSM-5 composite material, characterized in that: The following steps are involved: Step S1, preparation of Fe / Zr-MOF@ZSM-5: drying the support under vacuum at 80-100°C for 8-12h, pouring it into a formic acid solution, ultrasonicating it for 30-60min to form a solution A, dissolving FeCl3·6H2O and ZrCl4 in N,N-dimethylformamide to form a solution B, adding the solution B to the solution A, ultrasonicating it for 30-60min, adding 1,3,5-benzenetricarboxylic acid thereto, ultrasonicating it for 1-2h, transferring it to a high-pressure reactor, and heating it at 120-150°C for 24-48h; finally, washing the obtained sample with N,N-dimethylformamide and methanol for 3-5 times respectively, and drying it under vacuum at 80-100°C overnight to obtain Fe / Zr-MOF@ZSM-5; Step S2, preparing Fe2O3-ZrO2@ZSM-5: placing the Fe / Zr-MOF@ZSM-5 prepared in step S1 in a tube furnace for calcination to obtain Fe2O3-ZrO2@ZSM-5; Step S3: Preparation of SO 42 - / Fe2O3-ZrO2@ZSM-5: Add Fe2O3-ZrO2@ZSM-5 into sulfuric acid solution, soak for 30-180 min, filter to obtain solid, dry at 100-120℃ overnight, and finally calcine at 500-600℃ in air atmosphere for 3-6 h to obtain SO 42 - / Fe2O3-ZrO2@ZSM-5.
2. The method for preparing the Fe / Zr-MOF-assisted solid superacid @ZSM-5 composite material according to claim 1, characterized in that: The carrier in step S1 is ZSM-5.
3. The method for preparing the Fe / Zr-MOF-assisted solid superacid @ZSM-5 composite material according to claim 1, characterized in that: The mass ratio of ZrCl4, FeCl3·6H2O, 1,3,5-benzenetricarboxylic acid, formic acid, N,N-dimethylformamide, and ZSM-5 in step S1 is 1:(1-2):(1-3):(35-40):(25-30):(2-4).
4. The method for preparing the Fe / Zr-MOF-assisted solid superacid@ZSM-5 composite material according to claim 1, characterized in that: The calcination in step S2 is specifically as follows: heating to 500-600° C. at a heating rate of 5-10° C. / min in an air atmosphere, and the calcination time is 4-8 hours.
5. The method for preparing the Fe / Zr-MOF-assisted solid superacid@ZSM-5 composite material according to claim 1, characterized in that: The concentration of the sulfuric acid solution in step S3 is 1-3 mol / L.
6. The method for preparing the Fe / Zr-MOF-assisted solid superacid@ZSM-5 composite material according to claim 1, characterized in that: The mass ratio of Fe2O3-ZrO2@ZSM-5 and sulfuric acid solution in step S3 is 1:(20-50).
7. A Fe / Zr-MOF-assisted synthesized solid superacid@ZSM-5 composite material prepared by the preparation method of the Fe / Zr-MOF-assisted synthesized solid superacid@ZSM-5 composite material according to any one of claims 1 to 6.
8. An application of the Fe / Zr-MOF-assisted synthesized solid superacid@ZSM-5 composite material as described in any one of claims 1 to 6 in ammonia adsorption.
Citation Information
Patent Citations
A MOF-embedded activated carbon adsorbent material, its preparation method and application
CN113908809B
Preparation method and adsorbent for Cu-ZSM-5 / HKUST-1 composite honeycomb type VOCs wheel adsorbent
CN118122290B